2021
DOI: 10.2355/isijinternational.isijint-2021-037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Thermodynamic Driving Force and Effective Viscosity of Secondary Steelmaking Slags on the Dissolution of Al<sub>2</sub>O<sub>3</sub>-Based Inclusions from Liquid Steel

Abstract: Dissolution of Al 2 O 3 -based inclusions are paramount during production of special steel and slag engineering is key to enhance this phenomenon. This work evaluates the influence of thermodynamic driving force (ΔC) and effective viscosity (η e ) on steel cleanliness of three distinct steel grades and slag composition (Steel/Slag A, Steel/Slag B and Steel/Slag C). Initial and final steel and slag samples were withdrawal on an electric steelmaking facility. The first samples after addition of aluminum as deoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(90 reference statements)
1
4
0
Order By: Relevance
“…[25] The erosion of the furnace lining results in some MgO entering into the molten slag, and the increase in the contents of Al 2 O 3 and SiO 2 also decreases the MgO content in the slag, so the MgO content in the molten slag changes little. These results are basically consistent with those of Yang et al [25] The changes in average contents of the oxides and the corresponding R values in the Al 8) and (9).…”
Section: Formation Mechanism Of Type S Composite Inclusionssupporting
confidence: 92%
See 1 more Smart Citation
“…[25] The erosion of the furnace lining results in some MgO entering into the molten slag, and the increase in the contents of Al 2 O 3 and SiO 2 also decreases the MgO content in the slag, so the MgO content in the molten slag changes little. These results are basically consistent with those of Yang et al [25] The changes in average contents of the oxides and the corresponding R values in the Al 8) and (9).…”
Section: Formation Mechanism Of Type S Composite Inclusionssupporting
confidence: 92%
“…In recent years, some investigations on the formation of the inclusions in steel were carried out with thermodynamic analysis. [5][6][7][8][9][10][11] For example, Wang et al [7] investigated the effect of oxide component content on the low melting point zone in the Al 2 O 3 •SiO 2 •CaO•MgO system using FactSage software. It was found that the low melting point zone becomes wide with the increase in CaO content within the range of 0-30 mass% and the decrease in SiO 2 content within the range of 5-25 mass%.…”
Section: Introductionmentioning
confidence: 99%
“…Each chemical composition of the liquid phase resulting is then used as input data for the calculation of the viscosity in the Viscosity module. Phase diagram module for computation of phase equilibria in the quaternary phase diagram of CaO–SiO 2 –Al 2 O 3 –(0–15%) MgO slag were also used 14 , 17 , 24 , 25 , 27 , 28 , 50 .…”
Section: Methodsmentioning
confidence: 99%
“…From the Viscosity module (Melts database) is calculated the liquid slag viscosity (hl) 14 , 17 , 24 , 25 , 27 , 28 , 50 . This software uses the modified Quasichemical model (MQM), to describe the thermodynamic behavior of the liquid slag, which used quadruplet data detained from MQM, to calculate the viscosity of liquid 42 , 46 – 48 .…”
Section: Methodsmentioning
confidence: 99%
“…Elemental compositions of the tundish covering powders and of the rice hull ash, in wt.% (as-received industrial samples).height. The experiments were carried out in a resistive furnace 'HT-2100-Spezial'; details on this apparatus can be found in10 . The furnace works with a constant flux of argon (82 liters per hour) to avoid reoxidation by air.…”
mentioning
confidence: 99%